Use Of Mobile-Based Applications in The Services Public Transportation: Route Optimization and Provision of Efficient Services Through Applications (jalankemana) - Novia, Khusnul Febryla; Kurniawati, Andhiani; Wiranatakusuma, Dimas Bagus (Universitas Muhammadiyah Yogyakarta, 2023)
Indonesia has a large and growing population. Rapid population growth has led to increased mobility and the need for transportation to fulfill daily activities. Heavy traffic and congestion that often occurs in various cities in Indonesia are problems that affect the mobility and efficiency of public transportation. The purpose of this paper is to analyze the use of mobile-based applications in public transportation services in optimizing routes and providing efficient services through jalankemana applications. The data in the analysis of the use of mobile-based applications in public transportation services in optimizing routes and providing efficient services comes from data taken based on research results. This study used a survey research method, in which data were collected from respondents who were interviewed or filled out a questionnaire. The questionnaire will focus on the urgency related to the need for public transportation in the Yogyakarta area, especially Yogyakarta Muhammadiyah University students. Surveys can be conducted online or through direct interviews with students in Yogyakarta. The results of the study explain Jalankemana is a mobile application that provides information and services to assist users in planning trips using public transportation. JalanKemana can be a useful application for users who frequently use public transportation to plan their trips more efficiently. This app helps users navigate complex transportation systems, provides up-to-date information, and enables user collaboration to update relevant information.